Association between gut microbiota and onset of type 2 diabetes mellitus: a two-sample Mendelian randomization study - Zhang, Hongyan; Ma, Li; Peng, Wenbo; Wang, Bing; Sun, Yongning (Frontiers in Cellular and Infection Microbiology, 2024)
Aim Mendelian randomization (MR) analysis has been used in the exploration of the role of gut microbiota (GM) in type 2 diabetes mellitus (T2DM); however, it was limited to the genus level. This study herein aims to investigate the relationship of GM, especially at the species level, with T2DM in order to provide some evidence for further exploration of more specific GM taxa and pathway abundance in T2DM. Methods This two-sample MR study was based on the summary statistics of GM from the available genome-wide association study (GWAS) meta-analysis conducted by the MiBioGen consortium as well as the Dutch Microbiome Project (DMP), whereas the summary statistics of T2DM were obtained from the FinnGen consortium released data. Inverse variance weighted (IVW), MR-Egger, strength test (F), and weighted median methods were used to examine the causal association between GM and the onset of T2DM. Cochran’s Q statistics was employed to quantify the heterogeneity of instrumental variables. Bonferroni’s correction was conducted to correct the bias of multiple testing. We also performed reverse causality analysis. Results The corrected IVW estimates suggested the increased relative abundance of family Oxalobacteraceae (OR = 1.0704) and genus Oxalobacter (OR = 1.0874), respectively, were associated with higher odds of T2DM, while that of species faecis (OR = 0.9460) had a negative relationship with T2DM. The relationships of class Betaproteobacteria, family Lactobacillaceae, species finegoldii, and species longum with T2DM were also significant according to the IVW results (all P < 0.05). Conclusions GM had a potential causal association with T2DM, especially species faecis, finegoldii, and longum. Further studies are still needed to clarify certain results that are contradictory with previous findings.